Kapuściński passé? Ignacego Karpowicza trawestacja literackiego modelu pisarstwa mistrza reportażu a przemiany sceny komunikacyjnej - Rycombel, Marlena (Załącznik Kulturoznawczy, 2022)
Inspired by Zygmunt Ziątek’s reflection on the generational dimension of the defiance against the literary model of Ryszard Kapuściński’s repertorial writing, the author takes a close look at the book Nowy kwiat cesarza (i pszczoły) written by Ignacy Karpowicz. Nowy kwiat... is an intertextual reference to The Emperor. The book not only travesties adventure literary conventions present at the Kapuściński’s works, but also, thanks to gonzo reportage techniques, parodies the authenticity formula, widely present in Kapuściński’s writing after 1976. The authenticity formula that is based on the strong presence of narrator-author, plays a role of the objective testimony. The article employs the cultural perspective on the current discussion concerning the literariness of reportage.